Donnerjack - Zelazny, Roger (Avon Books, 1997)
A computer programmer falls in love with an artificial intelligence and when the intelligence dies follows her to the world of the dead. He obtains her release in exchange for which the couple will give up their first child, needed by the world of the dead for a special project.